Rationalizing key design decisions in the ATM user plane. - Grossman, Daniel B. (Computer communication review.)
Any technology requires some number of key design decisions. In the case of the ATM user plane, the choices to use fixed length, 53 byte cells and virtual connections were unorthodox from the perspective of many in the networking research community. This paper attempts a technical justification for those design decisions.